A Synthesis of Organizational Management Components of Administrators: A Review of Related Theories - KHAMMAVONG, Khone; VATHANAVONG, Thongthiane; SOULIVONG, Phetsamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
In the current context of rapidly changing organizational administration, having a scientifically sound and high-quality tool is crucial for evaluating and developing the administrative functions of executives to ensure their effectiveness.Therefore, the main objectives of this research are: 1) to synthesize the components of organizational administration for administrators, and 2) to determine the quality of the tool used for assessing administrators' organizational administration. The study employed a Content Analysis research methodology along with quantitative data. The target groups for this research were documents related to theories and policy guidelines on organizational administration, and a group of 30 administrators and staff affiliated with the National Institute of Justice, Luang Prabang Branch. Data were analyzed using Descriptive Analysis and basic statistics, including Mean, Standard Deviation, and Cronbach's Alpha Coefficient Reliability. The study findings revealed that: 1) the components of organizational administration for administrators consisted of 7 elements: (1) Planning, (2) Organizing, (3) Staffing/Personnel Administration, (4) Directing/Leading, (5) Coordinating, (6) Reporting, and (7) Budgeting. 2) The quality of the tool used for assessing administrators' organizational administration showed an overall index of item-objective congruence (IOC) of 0.91, with all components ranging from 0.67 to 1.00. The Cronbach's Alpha Reliability Coefficient was 0.850. The results indicate that the developed tool possesses good quality and can be further utilized to assess the actual state of organizational administration by administrators.